Interplay between network configurations and network governance mechanisms in supply networks a systematic literature review - Habib, Farooq (Cranfield University, 2012)
Purpose: This work systematically reviews the extant academic management literature on supply networks. It specifically examines how network configurations and network governance mechanisms influence each other in supply networks. Design: 125 analytical and empirical studies were identified using an evidence-based approach to review the literature mainly published between 1985 and 2012. Synthesis: Drawing on a multi-disciplinary theoretical foundation, this work develops an integrative framework to identify three distinct yet interdependent themes that characterize the study of supply networks: a) Network Configurations (structures and relationships); b) Network Governance Mechanisms (formal and informal); and c) The Interplay between Network Configurations and Network Governance Mechanisms. Findings: Network configurations and network governance mechanisms mutually influence each other and cannot be considered in isolation. Formal and informal governance mechanisms provide better control when used as complements rather than as substitutes. The choice of governance mechanism depends on the nature of exchange; role of management; desired level of control; level of flexibility in formal contracts; and complementary role of formal and informal governance mechanism. Research implications: This nascent field has thematic and methodological research opportunities for academics. Comparative network analysis using longitudinal case studies offers a rich area for further study. Practical Implications: The complexity surrounding the conflicting roles of managers at the organisation and network levels poses a significant challenge during the development and implementation stage of strategic network policies. Originality/value: This review reveals that formal and informal governance mechanisms provide better control when used as complements rather than as substitutes.
Keywords: Systematic literature review; supply chain management; trust; power; structures; relationships